Impact of residual urine volume decline on the survival of chronic hemodialysis patients in Kinshasa. Issue 1 (December 2016) - Mokoli, Vieux; Sumaili, Ernest; Lepira, François; Makulo, Jean; Bukabau, Justine; Izeidi, Patrick; Luse, Jeannine; Mukendi, Stéphane; Mashinda, Désiré; Nseka, Nazaire
Abstract Background Despite the multiple benefits of maintaining residual urine volume (RUV) in hemodialysis (HD), there is limited data from Sub-Saharan Africa. The aim of this study was to assess the impact of RUV decline on the survival of HD patients. Methods In a retrospective cohort study, 250 consecutive chronic HD patients (mean age 52.5 years; 68.8% male, median HD duration 6 months) from two hospitals in the city of Kinshasa were studied, between January 2007 and July 2013. The primary outcome was lost RUV. Preserved or lost RUV was defined as decline RUV < 25 (median decline) or ≥ 25 ml/day/month, respectively. The second endpoint was survival (time-to death). Survival curves were built using the Kaplan-Meier methods. We used Log-rank test to compare survival curves. Predictors of mortality were assessed by Cox proportional hazards regression models. Results The cumulative incidence of patients with RUV decline was 52, 4%. The median (IQR) decline in RUV was 25 (20.8–33.3) ml/day/month in the population studied, 56.7 (43.3–116.7) in patients deceased versus 12.9 (8.3–16.7) in survivor patients (p  < 0.001). Overall mortality was 78 per 1000 patient years (17 per 1000 in preserved vs 61 per 1000 lost RUV). Forty six patients (18.4%) died from withdrawal of HD due to financial constraints. The Median survival was 17 months in the whole group while, a significant difference was shown between lost (10 months, n  = 119) vs preserved RUV group (30 months, n  = 131;p  = 0001). Multivariate Cox proportional hazards models showed that, decreased RUV (adjusted HR 5.35, 95% CI [2.73–10.51], p  < 0.001), financial status (aHR 2.23, [1.11–4.46], p  = 0.024), hypervolemia (a HR 2.00, [1.17–3.40], p  = 0.011), lacking ACEI (aHR 2.48, [1.40–4.40], p  = 0.002) or beta blocker use (aHR 4.04, [1.42–11.54], p  = 0.009), central venous catheter (aHR 6.26, [1.71–22.95], p  = 0.006), serum albumin (aHR 0.93, [0.89–0.96], p  < 0.001) and hemoglobin (aHR 0.73, [0.63–0.84], p  < 0.001) had emerged as the independent predictors of all-cause mortality. Conclusion More than half of HD patients in this cohort study experienced fast RUV decline which contributed substantially to increase mortality, highlighting the need for its prevention and management.